Density, Viscosity, Refractive Indices, Ultrasonic Velocities and Thermo Acoustical Parameters of Acetophenone + Isoamyl Acetate at 303.15, 313.15 and 323.15 K - Saravanakumar, K.; Baskaran, R.; Kubendran, T.R. (Asian Journal of Chemistry, 2011)
The studies of density, viscosity, refractive indices and ultrasonic velocities are being increasingly used as tools for investigation of the properties of pure components and the nature of intermolecular interactions between the liquid mixture constituents. Density ( r), viscosity (h), refractiveD) and ultrasonic velocities (U) have been measured for the binary liquid mixture of indices (n acetophenone + isoamyl acetate over the entire composition range at 303.15, 313.15 and 323.15 K. This study involves the evaluation of different thermo acoustical parameters along with the excess properties. The Redlich-Kister model was used to correlate the measured excess properties. The molecular interactions existing between the components were also discussed.